Pemanfaatan Daun Ketapang, Daun Jambu Biji dan Daun Jarak sebagai Pewarna Alami pada Pembuatan Ecoprint Teknik Iron Blanket - Haq, Arina (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Natural textile dyes have a character that tends to be dull, so innovation is needed for maximum results. One of them is by combining leaves that have strong tannins with weak tannins, resulting in a new color composition. The purpose of this study is to describe the results of natural coloring of a combination of 3 leaves, ketapang, guava and distance. This study uses an experimental approach with a qualitative approach, with experimental and observational data collection methods, documentation and literature. The process begins with making dye extracts from the three leaves, the sourching process on the fabric, the mordunting process, the process of soaking the blanket cloth in a dye solution overnight, the process of arranging the leaves on the cloth that has been bitten, and covering with a blanket cloth that has been soaked with a solution of foliage dye extract. The process of rolling the cloth and steaming for 2 hours, and aerating for one night, the fixation process by applying a lime solution. The results of the experiment of combining 3 kinds of leaves on rayon twill fabric produced a light grayish-green color but intense so that the motif of the leaf bones is clearly visible, the color can be absorbed evenly and well. To get the maximum result, the color is flat and perfectly absorbed optimally using rayon twill cloth and the extra mordant process using soda ash, sodium acetate and tunjung must be implemented properly so that the 3 types of colors that have been absorbed can be easily transferred.